Heterogeneity and Function of Kupffer Cells in Liver Injury - Li, Weiyang; Chang, Na; Li, Liying (Frontiers in Immunology, 2022)
Kupffer cells are key regulators of liver immunity composing the principal part of hepatic macrophages even body tissue macrophages. They reside in liver sinusoids towards the portal vein. The micro-environment shapes Kupffer cells unique immunosuppressive features and functions. Kupffer cells express specific surface markers that distinguish from other liver macrophages. By engulfing gut-derived foreign products and apoptotic cells without triggering excessive inflammation, Kupffer cells maintain homeostasis of the liver and the body. Heterogeneity of Kupffer cells has been identified in different studies. In terms of the origin, adult Kupffer cells are derived from progenitors of both embryo and adult bone marrow. Embryo-derived Kupffer cells composed the majority of Kupffer cells in healthy and maintain by self-renewal. Bone marrow monocytes replenish massively when embryo-derived Kupffer cell proliferation are impaired. The phenotype of Kupffer cells are also beyond the traditional dogma of M1 and M2 type. Functionally, Kupffer cells play central roles in the pathogenesis of acute and chronic liver injury. They contribute to each pathological stage of liver disease. Kupffer cells might initiate inflammation, regulate fibrosis, cirrhosis and tumor cell proliferation, also contribute to the repairing. The underlying mechanism varied by damage factors and the pathology. Understanding the characteristics and functions of Kupffer cells may provide opportunities for the therapy of liver injury. Herein, we attempt to afford insights on heterogeneity and functions of Kupffer cells in liver injury using the existing findings.